2021
DOI: 10.1016/j.nicl.2021.102805
|View full text |Cite
|
Sign up to set email alerts
|

Potential contribution of pineal atrophy and pineal cysts toward vulnerability and clinical characteristics of psychosis

Abstract: Highlights Pineal morphology was investigated in schizophrenia patients and ARMS subjects. Pineal volumes were significantly smaller in both groups than in healthy controls. Pineal cysts were associated with clinical symptomatology in schizophrenia. Pineal morphology may reflect vulnerability and the clinical subtype of psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…As summarized in Table 1 , 63 schizophrenia patients, 57 individuals with ARMS, and 61 healthy controls were enrolled in the present study. Recruitment strategies (e.g., inclusion/exclusion criteria) and sample characteristics were fully described elsewhere ( 16 , 23 ); none of the participants had a history of serious medical issues (e.g., thyroid disease, diabetes, and serious head injury), severe obstetric complications, or substance abuse. A clinical diagnosis of schizophrenia was confirmed at Toyama University Hospital by experienced psychiatrists using the Structured Clinical Interview for DSM-IV Axis I Disorders Patient Edition ( 24 ) and that of ARMS using the Comprehensive Assessment of ARMS ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized in Table 1 , 63 schizophrenia patients, 57 individuals with ARMS, and 61 healthy controls were enrolled in the present study. Recruitment strategies (e.g., inclusion/exclusion criteria) and sample characteristics were fully described elsewhere ( 16 , 23 ); none of the participants had a history of serious medical issues (e.g., thyroid disease, diabetes, and serious head injury), severe obstetric complications, or substance abuse. A clinical diagnosis of schizophrenia was confirmed at Toyama University Hospital by experienced psychiatrists using the Structured Clinical Interview for DSM-IV Axis I Disorders Patient Edition ( 24 ) and that of ARMS using the Comprehensive Assessment of ARMS ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…As detailed previously ( 16 , 23 ), all subjects were scanned by a 3.0-tesla MR scanner (Magnetom Verio, Siemens, Erlangen, Germany) at Toyama University Hospital; a 3-D MPRAGE sequence was applied to obtain T1-weighted 1.2-mm consecutive sagittal images with a voxel size of 1.0 × 1.0 × 1.2 mm. The following parameters were used: TR/TE = 2300/2.9 ms, flip angle = 9°, field of view = 256 mm, and matrix = 256 × 256 pixels.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, melatonin is advantageous due to its low cost, minimal side effects, lack of drug interactions, and easy availability (Moon, Kim, Partonen, & Linnaranta, 2022). Imaging studies have revealed that patients with schizophrenia exhibit more severe pineal gland calcification and smaller parenchymal volume, suggesting a potential link between pineal gland calcification and the regulation of schizophrenia by melatonin (Takahashi et al, 2021).…”
Section: Schizophreniamentioning
confidence: 99%